Peran Kinerja Keuangan terhadap Luas Pengungkapan tanggung Jawab sosial Perusahaan (CSR) - Kholis, Nur (STIE Surakarta, 2013)
The annual report is one of the sources of information in order to get overview of the companys performance. This information is provided by the management company to the shareholder. Management performance has impact on the liquidity and volatility of stock prices, which form the basis by investors in making the investment.Disclosure of environmental performance, social, and economic development in the annual report is to reflect the level of accountability, responsibility, and corporate transparency to investors and other stakeholdersThe fact the issue of Corporate Social Responsibility of the company in Indonesia and the contradictory results of previous studies on the relationship of CSR and corporate performance as well as the variation of the problem raises the question of